Analysis of the alignment angles and flexion angle in women with patellofemoral pain syndrome (2017)
Patellofemoral pain syndrome (PFPS) is one of the most com-mon disorders in the knee that occurs with a higher incidence in women than men. Q-angle and A-angle as well as alignment and flexion angle of bending were considered in this study as kinematic variables. The hypothesis is that patients with changes in alignment variables are more likely to have pain in the patellofemoral joint. To verify this, we worked with patients with PFPS which was compared with control patients. No significant difference in angle A and the flexion angle of the knee were found, but a significant difference was found in Q-angle